Statistical analysis of energy absorption in aluminum foam sandwich under impact testing using the Taguchi design - Al Hazza, Muataz Hazza Faizi; Endut, Amalina; Adesta, Erry Yulian Triblas; Ibrahim, Nur A B; Ali, Mohammad Yeakub (Elsevier, 2018)
Selection of material in industrial application plays an important role in order to sustain the safety, performance and cost reduction. One of the new technologies that had been introduced recently was the aluminium foam sandwich (AFS) in which it is made from two aluminium skin or sheets with a core made by aluminium foam. AFS has advantages due to lightweight and high energy absorption properties. However, to use these new materials need to understand the energy absorption behavior. The aim of this research is to analyse the effect of the core and skin thickness on energy absorption of AFS using statistical tools. Three levels of skin and core thickness had been selected for charpy impact test by using Taguchi method. L9 orthogonal array have been used to run the experiments. The designation was in rectangular shape with dimension width, 13 mm and length, 64 mm based on ASTM D4812. The impact velocity is maintained at 3.35 m/s.